2008
DOI: 10.1007/s11884-008-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation in the treatment of neurogenic bladder dysfunction

Abstract: Voiding and storage of urine are performed by the urinary bladder and the urethra, which are neurally controlled by the sacral nerves. Neurologic disturbances can infl uence switching between storage and voiding that results in voiding dysfunction, leading to neurogenic bladder. Causes of neurogenic bladder dysfunction include spinal cord injury or trauma; central nervous system tumors; demyelinating disease involving the spinal cord; spinal cord ischemia; cerebral palsy; and myelomeningocele, which is the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
0
5
0
Order By: Relevance
“… 35 Nonetheless, these complicated surgical procedures and their related side effects, as well as the associated costs, may well be unacceptable to some patients. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 35 Nonetheless, these complicated surgical procedures and their related side effects, as well as the associated costs, may well be unacceptable to some patients. 36 …”
Section: Discussionmentioning
confidence: 99%
“…He concluded that sensory and motor nerves of the anterior roots conduct impulses, while the posterior nerve roots responsible for vital functions [5].…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, McGuire and colleagues first reported the posterior tibial nerve electrical stimulation [5]. Many other studies reported the use of PTNS in neurogenic and nonneurogenic patients with urgency, frequency, urge incontinence and voiding dysfunctions [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations